(untitled) (Sustainability in Debate, 2013)
The journal Sustainability in Debate (SeD), interdisciplinary in its scope, publishes original texts about the several dimensions of sustainability. It goal is to create a direct channel for debates about sustainable development, environmental management, socioenvironmental conflicts, the state of the environment, environmental governance, among other matters. We request that authors submit their manuscripts according to the information and requirements present in this document.